Using high organic carbon materials to manipulate soil microbiology for improved nitrogen bioavailability from anaerobic digestate - van Midden, Christina (Cranfield University, 2024)
Anaerobic digestate is a by-product of biogas production, often used as a fertiliser due to its high nitrogen content. However, nitrogen losses from its application leads to environmental pollution. The aim of this PhD project was to add agronomic value to anaerobic digestate and reduce its environmental impact by understanding the microbial mechanisms associated with improving its nutrient use efficiency by crops. Digestate with a high organic carbon content is known to stimulate microbial growth and the immobilisation of nitrogen into soil microorganisms. However, after phase separation the liquid fraction contains large quantities of nitrogen in bioavailable forms but has reduced organic carbon. Soil incubation experiments were designed to determine the type (i.e. labile or recalcitrant) and rate of organic carbon required to stimulate microbial immobilisation of nitrogen from liquid digestate. A polytunnel pot experiment with spring barley and a field experiment with sugar beet tested the addition of two carbon additives (straw and glycerol) selected from the previous experiments on plant growth and nitrogen use efficiency. The addition of glycerol increased microbial biomass carbon within a month from application in both experiments, however there was no subsequent increase in crop yield or nitrogen uptake, nor were N2O emissions and ammonia volatilisation affected. This indicates that either the carbon rate was too low to stimulate a nitrogen immobilisation that was significant enough to impact crop nitrogen uptake or that nitrogen remineralised too rapidly to be of benefit to later key nitrogen demanding crop growth stages. Future studies need to focus on determining the optimal amount of carbon to add with digestate to positively impact yield and reduce nitrogen losses. In conclusion this PhD thesis demonstrated a proof of concept that materials high in organic carbon content can be used to temporally immobilise digestate supplied nitrogen within the soil microbial biomass.
Harris, Jim A. - Associate Supervisor Sizmur, Tom - Associate Supervisor - University of Reading Shaw, Liz - Associate Supervisor - University of Reading
Keywords: Biogas residue; crop production; organic fertiliser; nitrogen immobilisation; microbial community; glycerol; straw; nitrogen use efficiency; PLFA